Levofloxacin Detection Using l-Cysteine Capped MgS Quantum Dots via the Photoinduced Electron Transfer Process - Hashmi, S. Z. H.; Dhiman, Tarun Kumar; Chaudhary, Navneet; Singh, Avinash Kumar; Kumar, Rahul; Sharma, Jai Gopal; Kumar, Anil; Solanki, Pratima R. (Frontiers in Nanotechnology, 2021)
Antibiotics resistance is becoming one of the biggest problems of the 21st century. The prior detection of antibiotics resistance can help human beings in better treatment of diseases. Here, we have used l-Cysteine capped magnesium sulfide quantum dots (L-Cyst-MgS QDs) to detect Levofloxacin antibiotic. L-Cyst-MgS QDs were synthesized using the hydrothermal method. Transmission electron microscopy study showed monodispersed L-Cyst-MgS QDs of 2–4 nm in size. Energy dispersive x-ray photoemission spectroscopy study confirmed the elemental composition of the L-Cyst-MgS QDs without any impurity. UV-vis absorption study showed a peak centered around 340 nm. The photoluminescence study exhibited the maximum peak at 410 nm for 340 nm of excitation wavelength. L-Cyst-MgS QDs were studied with thirteen antibiotics, namely Thiamphenicol, Gentamicin, Erythromycin, Ofloxacin, Ampicillin, Ciprofloxacin, Tetracycline, Chloramphenicol, Florfenicol, Amoxicillin, Moxifloxacin, Norfloxacin, and Levofloxacin. Among these, Levofloxacin showed the most significant change in the peaks’ intensity and was further used for the interaction study. In the interaction study, the peak corresponding to MgS showed a continuous decrease, while the peak corresponding to Levofloxacin showed an increase with the increased concentrations (0–100 μg/ml) of Levofloxacin. Linear behavior was obtained in the range of 1–90 μg/ml. FT-IR study confirmed the interaction of the Levofloxacin with L-Cyst-MgS QDs. The Time-resolved fluorescence spectroscopy showed identical lifetime for both the samples and no spectral overlap confirm the FRET free system. The underlying mechanism is explained based on the electron transfer from the conduction band of the L-Cyst-MgS QDs to the HOMO of Levofloxacin. The limit of detection was found to be 0.21 μg/ml.